Adaptive decision support system for estimating financial risks - Kozhukhivska, O.; Bidyuk, P.; Kozhukhivskyi, А. (Видавництво Львівської політехніки, 2015)
A computer based decision support system is proposed the basic tasks of which are adaptive model constructing and forecasting of financial risks. The DSS development is based on the system analysis principles, i.e. the possibility for taking into consideration of some stochastic and information uncertainties, forming alternatives for models and forecasts, and tracking of the computing procedures correctness during all stages of data processing. A modular architecture is implemented that provides a possibility for the further enhancement and modification of the system functional possibilities with new forecasting and parameter estimation techniques. A high quality of final result is achieved thanks to appropriate tracking of the computing procedures at all stages of data processing during computational experiments: preliminary data processing, model constructing, and forecasts estimation. The tracking is performed with appropriate set of statistical quality parameters. Examples are given for estimation of financial credit. The examples solved show that the system developed has good perspectives for the practical use. It is supposed that the system will find its applications as an extra tool for decision making when developing the strategies for financial companies and enterprises of various types.
Keywords: mathematical model; system analysis principles; adaptive forecasting; decision support system; risk estimation